THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND TAX AVOIDANCE ON FIRM VALUE MODERATED BY PROFITABILITY - Amalia, Anisa; Yuniarwati , Yuniarwati (Graduate Program of Universitas Tarumanagara, 2023)
This investigation's goal is to investigate and determine the impact of corporate social responsibility (CSR) and tax avoidance on firm value, which is tempered by profitability. This study employs a purposive sampling strategy based on empirical investigations on banking firms from 2018 to 2020, with a total sample of 84 banking organizations. The data in this study was analyzed using the Econometric Views (EViews) version 12 programs and Moderated Regression Analysis (MRA). The findings of this study show that corporate social responsibility (CSR) has a considerable positive effect on business value, but profitability cannot increase this effect. Tax evasion has no effect on firm value, but profitability can strengthen the effect of tax avoidance on firm value.